Investigation of optical, electrical and magnetic properties of hexagonal NiTiO3 nanoparticles prepared via ultrasonic dispersion techniques for high power applications. (25th May 2018) - Karmakar, Subrata; Manna, Ashis Kumar; Varma, Shikha; Behera, Dhrubananda
Abstract: Nickel titanate (NiTiO3 ) nanoparticles were synthesized by ultrasonic dispersion techniques using ethylene glycol monoetheline ether as a solvent. The x-ray diffraction (XRD), Raman, transmission electron micrographs (TEM) exhibit pure phase formation, fine hexagonal nanostructure, agglomerated and inhomogeneous grain growth in nm range (26.5 nm) of as-prepared NiTiO3 nanoparticles. Raman studies on NiTiO3 nanoparticles exposed almost all the active vibrational modes (5Ag + 5Eg ) of its crystalline structure. A wide optical band gap (3.02 eV) was observed from UV-DRS spectra which arises from the hybridized Ni- 3d and O- 2p orbitals to the Ti -3d orbitals. The characteristics vibration bands of M-O (Ni–O, and Ti–O) were also analyzed using Fourier Transform Infrared spectrum. The antiferromagnetic (AFM) properties were examined from M-H loop with coercive field 75.02 ± 0.05 Oe and saturation magnetization 0.418 ± 0.05 emu gm −1 . respectively. The dielectrics constant and loss decays with high frequency evaluation and Maxwell–Wagner type of polarization were responsible for its dielectric behavior. The total conductivity was explained using NNH and VRH hopping relaxation model and dc activation energy (0.81 eV) were calculated from Arrhenius plot.